PENGARUH KINERJA KEUANGAN, TINGKAT BUNGA DAN INFLASI TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - RIZKI DEFAWANTI, ALIFYANI; SISTA PARAMITA, R.A. (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to determine the factors that effect the stock returns of the company in Property and Real Estate sector. The population in this study were 48 companies with as many as 31 companies research samples are taken using purposive sampling . This study using financial ratios, interest rate and inflation than analyzed using multiple linier regression. Financial ratios can describe the condition of company so, financial ratio can be taken into consideration investors to conduct investment activities. F test result in this study indicate that jointly financial performance, interest rate and inflation effect the stock return. The results obtained for t test show that the variables ROA, Current Ratio, DER, TATO, EPS, and EVA have no effect on stock return. Variable beta has a significant negative while interest rate and inflation have a significant positive effect on stock return. Keywords: stock return, financial performance, interest rate, inflation